The effect of cognitive intervention on stroke distance in age-group swimmers - Schmidt, A. C.; Ungerechts, B. E. (1st International Scientific Conference of Aquatic Space Activities, 2008)
Advanced age-group swimmers and their coaches try to optimize their individual swimming technique. Therefore the stroke distance is often mentioned as a criteria. If swimmers cover more distance stroke by stroke, their movements under water are more efficient. The base of a successful motion sequence is a well-structured mental representation. Mental representation can be visualized by using special software. Based on these results, special workouts have been designed. During a six-week training period the participating group worked precisely according the advised concept. As pre-and post-tests the swimmers worked on the computer and performed 25 meters freestyle starting in the water, as fast as they could. On the date of the post-test the swimmers had a mental representation that was more organized and made improvements in their swimming performance. The distance was covered at nearly same speed, but with a lesser stroke rate; the stroke distance therefore increased.